Berberine-Loaded Solid Lipid Nanoparticles for Oral Administration Prepared by High-Shear Homogenization - Van, Nguyen Hong; Thu Ha, Hoang Thi; Xuan Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Berberine (BBR) is a quaternary benzylisoquinoline alkaloid used for the local treatment of gastrointestinal tract diseases. Recently, a wide range of pharmacological properties of BBR have been reported, which include anticancer, metabolic regulation, cardiovascular protection, antihypertensive, antitumor, and neuroprotective effects. However, BBR has exhibited poor aqueous solubility and low permeability. Solid lipid nanoparticles were investigated for therapeutic improvement of BBR via oral administration. Therefore, this study aimed to prepare BBR-loaded solid lipid nanoparticles (BBR-SLNs) using the high-shear homogenization method. A lipid screen was performed, and formulation ingredients and processing parameters were evaluated. The characteristics of BBR-SLNs were evaluated, including particle size, particle size distribution, zeta potential, drug loading, and in vitro release profile. Specifically, the optimal BBR-SLNs had a reasonable size with a PDI value below 0.3, the absolute value of the zeta potential above 50 mV, and excellent entrapment efficiency (EE%) of nearly 95%. BBR-SLNs expressed a sustained release profile of BBR, especially in the initial period. The resulting BBR-SLNs could be considered as a potential drug delivery system to enhance BBR absorption in the human body.